FEATURES OF FORMATION AND DEVELOPMENT OF THE COMMON MARKET OF MORTGAGE LENDING IN THE EUROPEAN UNION - R. Khusikhanov (Вестник университета)
The article is devoted to the analysis of features of formation of the uniform market of mortgage lending in the European Union. The main approaches of the countries of the region to delivery of a mortgage from the point of view of her key parameters are analysed. Value of the securities provided with a housing mortgage is revealed.